The Mother-Infant Attachment Process in Adoptive Families - Portello, Jacqueline Y. (Canadian Journal of Counselling and Psychotherapy, 1993)
This article addresses issues relevant to mother-infant attachment in adoptive families. First, this paper presents a review of the literature on the attachment process between adopted children and their mothers. Existing empirical research is understood in relation to Bowlby's (1969) theoretical formulation of attachment, the basic thesis of which is that infants develop affectional bonds at specific ages of their development and therefore, the child's age at the time of adoption is an important determinant of secure mother-infant attachment. Second, recommendations are made for future research in the area of parent-child attachment in adoptive families. Finally, this paper describes how counselling and educational practice may help to resolve attachment and developmental issues specific to adopted children.